1992
DOI: 10.1029/92wr00198
|View full text |Cite
|
Sign up to set email alerts
|

Econometric estimation of groundwater pumping costs: A simultaneous equations approach

Abstract: Recent studies have attempted econometric estimation of the effect of changing groundwater costs on various dimensions of agricultural behavior. These studies assume parametric cost values, ignoring the possibility that marginal pumping costs may be endogenous to the extent of pumping activity. Under the alternative assumption of increasing marginal pumping costs, existing estimates of various elasticities may be suspect due to specification bias. This paper investigates this possibility, modeling a pumping te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Similar types of responses were considered in an analysis of household water demand by Lund [1995], where a household's adaptations to shortages in water supply are decomposed into long-run changes in capital stock and short-run changes in management, such as installing a low-flush toilet and taking shorter showers, respectively. Previous studies have shown that an increase in water price leads to the adoption of precision (water conserving) irrigation systems by farmers [Caswell and Zilberman, 1986;Kanazawa, 1992;Green et al, 1996]. This research also shows that the relative profitability of different types of irrigation technologies is conditional on land quality characteristics.…”
Section: Empirical Modelmentioning
confidence: 58%
See 1 more Smart Citation
“…Similar types of responses were considered in an analysis of household water demand by Lund [1995], where a household's adaptations to shortages in water supply are decomposed into long-run changes in capital stock and short-run changes in management, such as installing a low-flush toilet and taking shorter showers, respectively. Previous studies have shown that an increase in water price leads to the adoption of precision (water conserving) irrigation systems by farmers [Caswell and Zilberman, 1986;Kanazawa, 1992;Green et al, 1996]. This research also shows that the relative profitability of different types of irrigation technologies is conditional on land quality characteristics.…”
Section: Empirical Modelmentioning
confidence: 58%
“…As mentioned above, previous papers have generally used programming models [Bontemps and Couture, 2002;Hooker and Alexander, 1998;Schaible, 1997]. Econometric estimates by Kanazawa [1992] use a much greater level of aggregation. While Moore et al [1994] do use farm-level data in their econometric analysis, the data we use has the advantage of covering an 8-year period, during which there was a rate change in water.…”
Section: Datamentioning
confidence: 99%
“…Suppose that Bureau ceilings bind at existing prices so that on the margin Bureau water is worth not $3.50/af but $50/af (see Kanazawa, 1993). Then, if water is worth $300/af in the cities, society is losing not $296.50/af on marginal water supplied to farms instead of cities but only $250/af (net of transportation costs, of course).…”
Section: Figurementioning
confidence: 99%
“…Analyzing pump taxes in light of the implications of entitlement ceilings for water use involves assuming that supplemental groundwater is available in addition to Bureau water. Assume that ground-water pumping is subject to increasing marginal cost because pumping draws down groundwater locally, thereby increasing the amount of energy required to bring water to the surface (Kanazawa, 1992). For simplicity, assume that groundwater and Bureau water are of equal quality.…”
Section: Bureau Pricing Reform Vs Groundwater Pump Taxesmentioning
confidence: 99%
“…These studies assume that the marginal cost of pumping does not depend on the amount of water pumped. Kanazawa (1992) suggested in his study for Central California that the marginal pumping cost of groundwater may increase as the amount of pumping increases. For simplicity, the assumption of constant marginal cost of pumping is adopted here.…”
Section: Simulationmentioning
confidence: 99%